Penal Code, ch. 43, §§ 509, MONTGOMERY, CODE OF ORDINANCES 213, 223-29 (1888 Brown Printing Co.) (Montgomery, Alabama). - (:unkn) unknown (General Publisher, 1888)
Any person who uses fire arms of any kind while fighting in the streets, or other public place, (except in self defense or in the execution of law), must, on conviction, be fined not less than one nor more than one hundred dollars.
--
Keywords: DUELING